Zero Emissions in the Production of Hydrogen Fuel Using Seawater as the Main Resource Through the Artificial Leaf Tool: a Proposal for a Bibliographic Review - Paco Izarra, Karla Paola (2023)
Polluted air creates health problems for people, plants and animals today due to many factors in industrial cities and power generation projects, transportation and chemical industry and others. It is for this reason that this research in bibliographic review allows us to know the different solutions to produce hydrogen through the analysis of the Scopus database and the VOSviewer tool that allows us to analyze the data, considering the variables that are artificial leaf, hydrogen, production , clean energy through seawater, graphs and tables were obtained which provide us with an analysis of the number of publications, the countries that carry out these investigations and the bibliometric maps worldwide for a global analysis. The results allow us to analyze and learn about the different solutions and materials that are used to carry out artificial photosynthesis that develops the production of hydrogen by separating water molecules with the aim of emitting zero emissions and being able to use it in different applications such as fuel, energy electrical, industrial uses and others. The purpose of this research is to allow us to make better decisions to apply this methodology according to the materials that we have in greater scope and that is a promising future for a generation of the new industry for the following years, also considering the objectives of sustainable development and finally, motivate readers to continue with these investigations and be able to apply it with institutions in charge of combating this problem.